THE EFFECT OF LEADERSHIP, ORGANIZATIONAL COMMITMENT, AND COMPENSATION ON EMPLOYEE PERFORMANCE AT NGANJUK REGIONAL HOSPITAL - Moh Khoirul Anam; Ratna Wardani; Joko Prasetyo (The SDGS Forum Communication, 2025)
Employee performance is a key factor in achieving organizational goals, especially in the public service sector such as hospitals. This study aims to analyze the influence of leadership, organizational commitment, and compensation on employee performance at Nganjuk Regional Hospital. Effective leadership, high organizational commitment, and a fair compensation system are expected to increase employee motivation and job satisfaction, which will ultimately have a positive impact on their performance. This study uses a quantitative method with a cross-sectional approach. The research sample consisted of 262 employees who were selected using the accidental sampling technique. The data was collected by distributing online questionnaires to employees through the whatsapp messaging application with a Google Form link, then analyzed using multiple linear regression. This research discusses the influence of leadership, organizational commitment, and compensation, both simultaneously and partially, on employee performance. The results of the study show that leadership, organizational commitment, and compensation have a positive and significant effect on employee performance. The significance value obtained is 0.000 < (α=0.05) indicating that H0 is rejected and H1 is accepted. Leadership has the greatest influence, followed by organizational commitment and compensation. These findings support previous theories and research that employee performance is influenced by effective leadership, high organizational commitment, and a fair compensation system. So, the implementation of effective leadership, increasing employee affective organizational commitment, and implementing a fair and transparent performance-based compensation system are considerations for the management of Nganjuk Regional Hospital to improve employee performance and the quality of hospital services.